Assessment of pharyngeal airway space with MRI In oral submucous fibrosis: A cross-sectional observational study - Ragavendiran Anandan; Krithika C. Lakshmi; Anuradha Ganesan; Yesoda AniyanK (Elsevier, 2024)
Introduction: Oral submucous fibrosis (OSMF) alters the pharynx, which may affect airway size. MRI will be useful for diagnosing pharyngeal abnormalities. MRI is used to evaluate pharyngeal airway and soft palate changes in OSMF patients. Materials and methods: This study is a cross-sectional observational study that included a sample size of 42 patients. Group A consisted of 21 patients with OSMF, while Group B consisted of 21 volunteers without OSMF, who served as the control group. The patients with OSMF were classified into Stages I, II, and III according to the categorization established by Pindborg JJ in 1989, Stop-Bang questionnaire was employed to assess obstructive sleep apnoea. Magnetic Resonance Imaging (MRI) was utilized to acquire evaluations of the pharyngeal airway, encompassing measurements in the midsagittal, cross-sectional width, length planes, and cross-sectional area with volume, for all participants. The Shapiro-Wilk test determines distribution normality. We utilized one-way ANOVA to compare the means between groups. Results: The average age of OSMF patients was 45.9 ± 8.16, while the control group was 39.19 ± 4.21. Stage I of OSMF had the highest mean Stop Bang questionnaire score (2.75), followed by stage III (2.22), and stage II (1.75). Statistically significant differences (p < 0.001) were seen in volume, linear midsagittal planes, cross-sectional width and length planes, cross-sectional area, and soft palate breadth and length between OSMF and control groups. Conclusion: MRI can effectively examine early changes in the pharyngeal airway of patients with OSMF thereby serving as a constructive diagnostic and motivational tool.